2021
DOI: 10.1016/j.exphem.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expression of microRNA-125a targets is required to induce murine hematopoietic stem cell repopulating activity

Abstract: MicroRNAs (miRs) are small noncoding RNAs that regulate gene expression posttranscriptionally by binding to the 3 0 untranslated regions of their target mRNAs. The evolutionarily conserved microRNA-125a (miR-125a) is highly expressed in both murine and human hematopoietic stem cells (HSCs), and previous studies have found that miR-125 strongly enhances selfrenewal of HSCs and progenitors. In this study we explored whether temporary overexpression of miR-125a would be sufficient to permanently increase HSC self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This led to increased clone longevity, size, contribution to multilineage engraftment, and trafficking from the BM to the circulation after transplantation (Wojtowicz et al, 2019 ). Continuous miR‐125a expression appears to be necessary to induce HSC proliferation and self‐renewal (Luinenburg et al, 2021 ). Other miR‐125 family members (miR‐125b1 and miR‐125b2), which share with miR‐125a the same seed sequence, exert similar effects on HSCs when overexpressed through retroviral vectors (Wojtowicz et al, 2014 ).…”
Section: Mirnas and Hsc Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to increased clone longevity, size, contribution to multilineage engraftment, and trafficking from the BM to the circulation after transplantation (Wojtowicz et al, 2019 ). Continuous miR‐125a expression appears to be necessary to induce HSC proliferation and self‐renewal (Luinenburg et al, 2021 ). Other miR‐125 family members (miR‐125b1 and miR‐125b2), which share with miR‐125a the same seed sequence, exert similar effects on HSCs when overexpressed through retroviral vectors (Wojtowicz et al, 2014 ).…”
Section: Mirnas and Hsc Stemnessmentioning
confidence: 99%
“…Temporary ex‐vivo miR‐125a overexpression has been proposed to exploit the beneficial effects of miR‐125 in enhancing HSC self‐renewal without the risk of inducing leukemia, with the aim of expanding HSCs for therapeutic purposes such as prior to transplant (Luinenburg et al, 2021 ). This strategy would be particularly useful when low HSC numbers are available such as in cord blood units (Wojtowicz et al, 2016 ).…”
Section: Mirnas Hscs and Therapymentioning
confidence: 99%
“…The miRNA-125 family members, including miR-125a, miR-125b1, and miR-125b2, are essential for the self-renewal and differentiation of HSCs [ 72 ]. Also, previous studies showed that miRNA-125a strongly increases the proliferation of HSCs and progenitors but reduces their apoptosis [ 73 , 74 ]. In this regard, a recent study showed that miR-125a enriched in the EVs derived from adult BM-MSCs has a principal role in ex vivo proliferation of HSCs/HPCs by regulation of apoptosis [ 75 ].…”
Section: Introductionmentioning
confidence: 99%